Antibacterial activities and biosynthesis of nanoparticles using hemp extracts - Karishma Singh; Roger M. Coopoosamy; Kubendran K. Naidoo; Jamila K. Adam (AOSIS, 2022)
Background: The use of plants in the biosynthesis of nanoparticles is a fast-growing technique and has gained much interest from researchers over the years. Aim: This study reported the utilisation of leaf extracts of Cannabis sativa L. (hemp) for the biosynthesis of silver nanoparticles (AgNPs). Methods: In this study, techniques such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) microanalysis and Fourier transform infrared (FT-IR) were carried out for the synthesis and characterisation of nanoparticles. The antibacterial efficacy of the synthesised nanoparticles was evaluated by using the agar diffusion and macrobroth dilution methods. The antibacterial properties of the biosynthesised AgNPs were evaluated against both Gram-negative and Gram-positive bacteria. Results: The formation of AgNPs was confirmed by colour change in plant extracts and further characterised by Ultraviolet-visible (UV-Vis) spectrophotometry TEM, SEM, EDX and FT-IR analyses. Fourier transform infrared analysis revealed the efficient capping and stabilisation properties of these particles and the nature of the capping agent. Silver nanoparticles prepared from leaf extracts showed effective antibacterial activity against Escherichia coli. Conclusion: Biosynthesised AgNPs showed a broad-spectrum antimicrobial susceptibility range and therefore represent promising antimicrobial agents. This is the first reported study for hemp leaf extracts and contributes to the environmentally friendly and cost-effective technique of biosynthesising nanoparticles for drug development. Contribution: This study contributes to the current medicinal properties of cannabis. Furthermore, it reflects that cannabis can also be utilized at a nanoscale with effective antibacterial efficacy.